2020
DOI: 10.3168/jds.2020-18721
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of a Saccharomyces cerevisiae fermentation product on heat-stressed dairy cows

Abstract: The objective of this study was to evaluate the effects of supplementing a Saccharomyces cerevisiae fermentation product (SCFP) on body temperature indices, metabolism, acute phase protein response, and production variables during heat stress (HS). Twenty multiparous lactating Holstein cows (body weight = 675 ± 12 kg; days in milk = 144 ± 5; and parity = 2.3 ± 0.1) were used in an experiment conducted in 2 replicates (10 cows/replicate). Cows were randomly assigned to 1 of 2 dietary treatments: control diet (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…This is in line with findings in calves and lambs where the SCPF feeding had no influence on the fraction of circulating immune cells subpopulations [ 15 , 25 ]. In contrast, according to the literature, SCFP supplementation raised the numbers of circulating leukocytes and neutrophils in heat-stressed cows [ 26 ] and the fraction of monocytes and B-cells in adult dogs [ 9 ]. These effects of SCFP supplementation on circulating immune cell populations indicate that SCFP feeding may not always lead to an altered blood immune cell composition and that species, age of the animals, feeding regimes, housing and other conditions affect the outcome of an SCFP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…This is in line with findings in calves and lambs where the SCPF feeding had no influence on the fraction of circulating immune cells subpopulations [ 15 , 25 ]. In contrast, according to the literature, SCFP supplementation raised the numbers of circulating leukocytes and neutrophils in heat-stressed cows [ 26 ] and the fraction of monocytes and B-cells in adult dogs [ 9 ]. These effects of SCFP supplementation on circulating immune cell populations indicate that SCFP feeding may not always lead to an altered blood immune cell composition and that species, age of the animals, feeding regimes, housing and other conditions affect the outcome of an SCFP supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, probiotics and prebiotics such as yeast extracts or galacto-oligosaccharides (GOSs) have been promoted as feed additives to enhance immunity and GIT health [ 111 ] in heat-stressed cows [ 60 , 112 , 113 ], birds [ 49 ], and rats [ 108 ]. In most of these studies, the benefits in productive parameters, health, and welfare of the animals as a result of supplementation with pro- and prebiotics were examined.…”
Section: Nutritional Interventions To Avoid or Lessen The Effects Of Heat Stressmentioning
confidence: 99%
“…Other studies observed that heat stress increased MUNs, and feeding SCCFSCCFs had no detectable effects on MUNs [12]. Heat-stressed cows mobilize skeletal muscle to provide amino acids to produce acute-phase proteins (Johnson, 2012) and glucose (Baumgard and Rhoads, 2013).…”
Section: Dmi Bw Milk Yield and Compositionmentioning
confidence: 99%
“…The other metabolic indices, including AST, ALT, glucose, triglyceride, cholesterol, and creatinine, were not affected by the SCCF supplementation or experimental TMRs. Some studies observed that the blood parameters were not affected by the S. cerevisiae treatment [12,27]. However, other studies reported that S. cerevisiae supplementation favorably influenced the energy metabolic status and might have a liver-protecting effect on high-yield cows [28,29].…”
Section: Serum Metabolites From Blood Samplesmentioning
confidence: 99%
See 1 more Smart Citation